PERANCANGAN SISTEM INFORMASI KOHORT IBU HAMIL MENGGUNAKAN MICROSOFT VISUAL STUDIO 2010 DI UPT PUSKESMAS PASEH KABUPATEN BANDUNG - Anita Putri Wijayanti; Indri Widya Epriyani; Emylia Fiskasari (POLITEKNIK PIKSI GANESHA, 2021)
This research aims to design a cohort information system for pregnant women using Microsoft Visual Studio 2010 at the UPT Puskesmas Paseh Bandung Regency. This research used qualitatif methods with a descriptive approach. Data collection methods used are observation, interviews and literature study. The development method used is Linear Sequential/Waterfall. Programming language using Microsoft Visual Studio 2010 and Microsoft Access 2016 as database. From the research conducted, there were promblems found are : (1) the cohort register was manual, (2) the absence of a more effective system to facilitate reporting, (3) reports are often damaged or even lost. (4) inadequate facilities and infrastructure. The suggestions given to solve this problem are : (1) there is a need for a computerized system, (2) there is a need for socialization and guidance to the employees concerned, (3) the application needs regular maintenance, (4) adequate facilities and infrastructure are needed to support reporting activities.